1994
DOI: 10.1093/jn/124.7.1060
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Bone Loss in Postmenopausal Women Supplemented with Calcium and Trace Minerals

Abstract: The effects of calcium supplementation (as calcium citrate malate, 1000 mg elemental Ca/d) with and without the addition of zinc (15.0 mg/d), manganese (5.0 mg/d) and copper (2.5 mg/d) on spinal bone loss (L2-L4 vertebrae) was evaluated in healthy older postmenopausal women (n = 59, mean age 66 y) in a 2-y, double-blind, placebo-controlled trial. Changes (mean +/- SEM) in bone density were -3.53 +/- 1.24% (placebo), -1.89 +/- 1.40% (trace minerals only), -1.25 +/- 1.46% (calcium only) and 1.48 +/- 1.40% (calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(83 citation statements)
references
References 12 publications
1
79
2
1
Order By: Relevance
“…Cu and Zn supplementation did not provide further benefit to bone compositional characteristics, and a priori contrasts indicate that the Cu and Zn supplement was detrimental by year 2 to any beneficial effect of the Ca and vitamin D supplementation. This finding was just the opposite of that of Strause et al (1) who found that a cocktail of Cu, Zn and Mn enhanced the effect of Ca supplementation on bone mineral density, and was not consistent with the finding that Cu supplementation prevented vertebral trabecular bone density loss (2) . Thus, a possible explanation for the discordant findings was sought.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Cu and Zn supplementation did not provide further benefit to bone compositional characteristics, and a priori contrasts indicate that the Cu and Zn supplement was detrimental by year 2 to any beneficial effect of the Ca and vitamin D supplementation. This finding was just the opposite of that of Strause et al (1) who found that a cocktail of Cu, Zn and Mn enhanced the effect of Ca supplementation on bone mineral density, and was not consistent with the finding that Cu supplementation prevented vertebral trabecular bone density loss (2) . Thus, a possible explanation for the discordant findings was sought.…”
Section: Discussioncontrasting
confidence: 85%
“…The inferior bone status is consistent with animal studies and premature infant supplementations showing that bone formation is impaired by a Cu-deficient state (3,4,6,7) . It is unclear why a positive response to the 2 mg/d Cu supplement was not obtained in women with Cu intakes , the RDA, which would be inconsistent with the findings of Strause et al (1) and Eaton-Evans et al (2) that Cu supplementation at about three times the RDA was beneficial to bone mineral density. Perhaps another environmental or nutritional factor promoting bone loss or poor Ca utilisation inhibited the response to Cu supplementation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Zinc deficiency in animals, including chicks, cows, pigs, monkeys, and rats results in delayed or defective mineralization, widened growth plates, indistinct zones of provisional calcification, and malformed bones (Hurley, 1981;Yamaguchi, 1998). Both copper and zinc supplementations have been shown to inhibit bone loss in adult humans (Strause et al, 1994;Eaton-Evans et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The zinc:copper ratios ranged from 1 to 53 in the experimental diets. Postmenopausal women were chosen to be subjects in the study because they were employed in studies showing an effect of copper (EatonEvans et al, 1996) and zinc (Strause et al, 1994) on bone loss, and because of their susceptibility to osteoporosis.…”
Section: Introductionmentioning
confidence: 99%